ANT 2008/09: AWI airborne Radio-Echo Sounding data over eastern Dronning Maund Land and East Antarctica and Berkner Island (RBI and WEGAS Projects) - Eisen, Olaf; Jokat, Wilfried; Steinhage, Daniel; Helm, Veit; Hindmarsh, Richard C A (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI EMR system during the Antarctic season of 2008/09. The profiles extend across the eastern Dronning Maud Land , the ice shelfes and Berkner Island. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.
Keywords: AWI EMR Radar; Berkner Island; Dronning Maud Land; East Antarctica; ice divide; Ice Sheet; Ice shelf; Polar 5; radio-echo sounding